All Tapped Out: Touchscreen Interactivity and Young Children’s Word Learning - Russo-Johnson, Colleen; Troseth, Georgene; Duncan, Charlotte; Mesghina, Almaz (Frontiers in Psychology, 2017)
Touchscreen devices differ from passive screen media in promoting physical interaction with events on the screen. Two studies examined how young children’s screen-directed actions related to self-regulation (Study 1) and learning (Study 2). In Study 1, 30 2-year-old children’s tapping behaviors during game play were related to their self-regulation (measured using Carlson’s snack task): girls and children with high self-regulation tapped significantly less during instruction portions of an app (including object labeling) than did boys and children with low self-regulation. Older preschoolers (N = 47, aged 4 to 6 years) tapped significantly less during instruction than 2-year-olds did. Study 2 explored whether the particular way in which 170 children (2 to 4 years of age) interacted with a touchscreen app affected their learning of novel object labels. Conditions in which children tapped or dragged a named object to move it across the screen required different amounts of effort and focus, compared to a non-interactive (watching) condition. Age by sex interactions revealed a particular benefit of dragging (a motorically challenging behavior) for preschool girls’ learning compared to boys, especially for girls older than age 2. Boys benefited more from watching than dragging. Children from low socioeconomic status (SES) families learned more object names when dragging objects versus tapping them, possibly because tapping is a prepotent response that does not require thoughtful attention. Parents and industry experts should consider age, sex, self-regulation, and the physical requirements of children’s engagement with touchscreens when designing and using educational content.